Top answers

Maths
A Level

Using the trigonometric identity (sinx)^2 + (cosx)^2 = 1, show that (secx)^2 = (tanx)^2 + 1 is also a trigonometric identity.

We can divide by (cosx)^2 across the identity (sinx)^2 + (cosx)^2 = 1 (which can be derived from properties of the unit circle and a bit of Pythagoras’ theorem) to achieve

[(sinx)^2 / (cosx)^2] + [...

Answered by Annie B. Maths tutor
3115 Views

The random variable J has a Poisson distribution with mean 4. Find P(J>2)

P(J>2) = P(J=0)+P(J=1)     [split it up]

P(X=t)= (V^t)/t!*e^V       where V=4 in this case  [use the formula]

P(J>2) = 4^0/0!*e^4 + 4^1/1!*e^4

          =1/e^4 + 4/e^4  =  5e^-4...

Answered by Nathan C. Maths tutor
3662 Views

3. The point P lies on the curve with equation y=ln(x/3) The x-coordinate of P is 3. Find an equation of the normal to the curve at the point P in the form y = ax + b, where a and b are constants.

P- (3,0) y=ln(x/3)     u=x/3    y=ln(u) ​​​​​​            du = 1/3  dy = 1/u = 3            dx       du dy= du x dy dx dx  du   = 1/3 x 3 = 1 gradient at normal = -1 equ...

Answered by Kaushalya B. Maths tutor
12013 Views

Differentiate 3x^(2)+xy+y^(2)=12 with respect to x

this is implicit differentiation. We start by differentiating 3x^(2) to get 6x (lower the power by 1, multiply by the original power). For xy, we use the product rule, giving us y + (x)dy/dx (this is the ...

Answered by Noyonika L. Maths tutor
3517 Views

How do I use the product rule for derivatives?

Imagine a function f(x)=g(x)*h(x)    [that is, two functions multiplied together]

To find the derivative, f'(x)=g'(x)*h(x) + g(x)*h'(x)    

For example, f(x) = (3x2)*(cos x )     ...

Answered by James W. Maths tutor
3330 Views

We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences